Application of Gas-Kinetic Unified Algorithm for Solving Boltzmann Model Equation with Vibrational Energy Excitation (Communications in Computational Physics, 2025)
In recent decades, the gas-kinetic unified algorithm (GKUA) is proposedto simulate the gas flow in the whole flow regimes. In previous studies, GKUA wasextended to problems of flows around the aircraft and internal flows considering theinfluence of rotational energy, as well as the flows around the aircraft considering theinfluence of vibrational energy. In this paper, we try to apply the model consideringthe effect of vibrational energy to the engine internal and external mixed flow problem,and build a numerical simulation framework of engine internal and external mixedflow considering the effect of vibrational energy. The reliability of the algorithm isverified by using one-dimensional shock tube problem and two-dimensional nozzleinternal flow problem. The results show that the model can describe the flow problemof high temperature nozzle internal flow. Then the two-dimensional nozzle internaland external mixed flow problem of 25N attitude control engine is studied, the unsteady evolution and non-equilibrium effect of the mixed flow field are analyzed, andthe flow parameter distribution of the mixed flow field without internal energy excitation, considering rotational energy excitation and considering vibrational energyexcitation are compared.